Memahami impulsive buying pada generasi z pengguna tiktok shop: tinjauan mediasi hedonic lifestyle dalam hubungan locus of control - Alya Zirahtu Nisyah; Aflah Zakinov Irta (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to examine the mechanism of the relationship between locus of control and impulsive buying among Generation Z users of TikTok Shop through the mediating role of hedonic lifestyle. A quantitative approach was used in the form of explanatory research. The study sample consisted of 349 respondents obtained using incidental sampling. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results of the analysis indicate that locus of control contributes positively and significantly to hedonic lifestyle. Furthermore, hedonic lifestyle was found to significantly increase impulsive buying. However, locus of control does not have a significant direct effect on impulsive buying. In the indirect effect test, it was found that hedonic lifestyle fully mediates the relationship between locus of control and impulsive buying. In conclusion, the tendency toward impulsive buying among Generation Z users of TikTok Shop is shaped more by hedonic lifestyle than by the direct influence of locus of control. Penelitian ini bertujuan untuk melihat mekanisme hubungan antara locus of control dan impulsivebuying pada Generasi Z pengguna TikTok Shop melalui peran mediasi hedonic lifestyle. Pendekatankuantitatif digunakan dengan jenis explanatory research. Sampel penelitian berjumlah 349 respondenyang diperoleh menggunakan teknik incidental sampling. Data dianalisis melalui Structural EquationModeling-Partial Least Squares (SEM-PLS). Hasil analisis menunjukkan bahwa locus of controlberkontribusi positif dan signifikan terhadap hedonic lifestyle (β = 0,844; t = 52,246; p < 0,000). Selainitu, hedonic lifestyle terbukti meningkatkan impulsive buying secara signifikan (β = 0,778; t = 12,576; p< 0,000). Namun, locus of control tidak berpengaruh signifikan secara langsung terhadap impulsivebuying (β = 0,055; t = 0,884; p = 0,377). Pada pengujian efek tidak langsung terlihat bahwa hedoniclifestyle terbukti memediasi secara penuh hubungan antara locus of control dan impulsive buying (β= 0,657; t = 12,056; p < 0,000). Kesimpulannya, kecenderungan impulsive buying pada Generasi Zpengguna TikTok Shop lebih banyak terbentuk melalui hedonic lifestyle dibandingkan melaluipengaruh langsung locus of control.